Workplace Trauma in a Digital Age: The Impact of Video Evidence of Violent Crime on Criminal Justice Professionals - Birze, Arija (Journal of interpersonal violence, 2023)
High-quality video and audio recordings of violent crimes, captured using now ubiquitous digital technologies, play an increasingly important role in the administration of justice. However, the effects of exposure to gruesome material presented in this form on criminal justice professionals who analyze, evaluate, and use this potentially traumatic content in the context of their work, are largely unknown. Using long interviews and constructivist grounded theory, this qualitative study sought to explore experiences of exposure to video evidence of violent crime among Canadian criminal justice professionals. Sixteen individuals including police, lawyers, judges, psychiatrists, law clerks, and court reporters volunteered to participate in qualitative long interviews asking about workplace exposures to violent videos. Themes identified address the ubiquity of video evidence of violent crime; proximity to violence through video; being blindsided through lack of preparedness for violent content; repeated exposures through multiple and protracted viewings; insufficient customary methods for self-protection; and the enduring impact of exposure to videoed violence. We determine that criminal justice professionals are increasingly and repeatedly presented with deeply disturbing imagery that was once imperceptible or unknowable and thus previously held at a greater distance. Elements of what is newly visible and audible in video evidence of violent crime create a new emotional proximity to violence that potentially increases the risks of secondary trauma and underscores the need for improved safety measures.